The Daughters of Ireland : Deverill Chronicles #2 - Montefiore, Santa, 1970- (New York, N.Y. : William Morrow, 2017)
In 1925, with the war over, Celia Deverill seeks to restore her ruined ancestral home, while her cousin Kitty must make a heartbreaking decision, and Bridie, the daughter of a former cook in Castle Deverill, plots revenge against a woman who wronged her in the past.
Keywords: Castles -- Ireland -- Fiction; Families -- Ireland -- Fiction; Castles -- Ireland -- Fiction; Family life -- Ireland -- Fiction; Ireland -- History -- 20th century -- Fiction; Ireland -- History -- 20th century -- Fiction; Domestic fiction; Historical fiction